PENGARUH SOLVABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN SUB SEKTOR PERBANKAN YANG TEDAFTAR DI BEI DARI TAHUN 2018-2019 - HEMAT SABRIANTO R SIGALINGGING; HISAR PANGARIBUAN (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
This study aims to examine the effect of solvency as measured by debt to asset ratio and debt to equity ratio on corporate social responsibility. The research method used in this study is a descriptive quantitative method using 41 banking companies listed on the Indonesia Stock Exchange from 2018-2019, therefore 123 research samples were observed. The data used is quantitative data derived from the company’s annual report. Corporate social responsibility is measured by content analysis of the company’s annual report on the disclosure of corporate social responsibility. Meanwhile, the debt to asset ratio is measured by calculating total debt divided by total assets for the current period, and the debt to equity ratio is measured by total debt divided by total equity for the current period. The results showed that the debt to asset ratio had a significant and positive effect on corporate social responsibility with a value of 0.015 <0.05, while the debt to equity ratio had a positive and insignificant effect on corporate social responsibility with a value of 1.208 > 0.05. Companies with high debt levels tend to make better corporate social responsibility disclosures to increase public trust in related companies.